Kenari: Meningkatkan Omzet Dengan Digital Marketing Terkini - Saiful Do. Abdullah; Muhammad Ridha Albar; Amal Khairan; Siti Hadjar A. Rahman; Andini Banuri (Universitas 45 Surabaya, 2024)
The community service program “KENARI: Increasing Turnover with Latest Digital Marketing” in Kayu Merah Village, Ternate City, aims to improve the understanding and application of digital marketing in the community. Through the KENARI (Kenali Adaptasi Realisasi) approach, this program provides socialization, practical guidance, and mentoring to help the community utilize social media in digital marketing. The stages include problem identification, adaptation of digital marketing solutions, and realization of marketing strategies. Target outputs include a socialization video, a service journal, and publications in local mass media. The implementation methods include problem identification, preparation of mentoring materials, socialization and coordination with the community, implementation of mentoring and socialization, and monitoring and evaluation of implementation. The implementation schedule and location map of target partners are also presented to support the success of this program.